The best spatial scale of firm innovation networks: Evidence from Shanghai high‐tech firms. (14th August 2018) - Cao, Xianzhong; Zeng, Gang; Teng, Tangwei; Si, Yuefang
Abstract: Innovation networks are the channel of firms' access to knowledge. Taking Shanghai high‐tech firms as a case study, this paper discusses the differences among biomedical, electronic information, new materials and equipment manufacturing firms from different spatial scales such as the global, local, and glocal. The spatial scale of firm innovation networks is divided into global, national, city and glocal scales The efficiency of national innovation networks is the highest, followed by glocal innovation networks, while city and global innovation network efficiency is lower. The efficiency of high‐tech firm innovation networks is affected by industrial characteristics and spatial distance. The differences in efficiency among innovation networks of Shanghai high‐tech firms are significant.